2013
DOI: 10.1186/2049-2618-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Murine norovirus infection does not cause major disruptions in the murine intestinal microbiota

Abstract: BackgroundMurine norovirus (MNV) is the most common gastrointestinal pathogen of research mice and can alter research outcomes in biomedical mouse models of inflammatory bowel disease (IBD). Despite indications that an altered microbiota is a risk factor for IBD, the response of the murine intestinal microbiota to MNV infection has not been examined. Microbiota disruption caused by MNV infection could introduce the confounding effects observed in research experiments. Therefore, this study investigated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
2
25
1
3
Order By: Relevance
“…Consistent with a previous report 52 , CR6 infection had no effect on luminal or colon-associated microbial communities in STAT1-sufficient animals. However, maintenance of colonic-tissue associated community structure was STAT1-dependent, which we considered indicative of potential bacterial translocation that could contribute to CR6-induced pathology.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with a previous report 52 , CR6 infection had no effect on luminal or colon-associated microbial communities in STAT1-sufficient animals. However, maintenance of colonic-tissue associated community structure was STAT1-dependent, which we considered indicative of potential bacterial translocation that could contribute to CR6-induced pathology.…”
Section: Discussionsupporting
confidence: 92%
“…A subset (20%) of HNoV-infected individuals exhibited enhanced F/B ratios [87], while MNV-1 enhanced F/B ratios in C57BL/6 mice at Day 5 postinfection [88]. However, longitudinal analyses of both C57BL/6 (MNV-1, MNV.CR6) and Swiss Webster (MNV-1, MNV-4) mice failed to detect MNoV-induced dysbiosis of gastrointestinal bacteria at the phylum level [89]. A reduction in intestinal Lactobacillus strains occurred in MNV1-infected ICR mice, with a concurrent increase in Proteobacteria delta , mirroring findings from HNoV [89].…”
Section: Interactions Of Nov With the Microbiotamentioning
confidence: 99%
“…However, longitudinal analyses of both C57BL/6 (MNV-1, MNV.CR6) and Swiss Webster (MNV-1, MNV-4) mice failed to detect MNoV-induced dysbiosis of gastrointestinal bacteria at the phylum level [89]. A reduction in intestinal Lactobacillus strains occurred in MNV1-infected ICR mice, with a concurrent increase in Proteobacteria delta , mirroring findings from HNoV [89]. On the flip side, experimentally induced bacterial dysbiosis also alters MNoV infection.…”
Section: Interactions Of Nov With the Microbiotamentioning
confidence: 99%
“…Conflicting reports exist whether MuNoV infection alters the composition of the microbiota in immunocompetent mice. No major changes were observed in the intestinal microbiota of inbred C57BL/6 or outbred Swiss Webster mice infected with MNV-1, MNV-4, or CR6 (145). In another study, a significant reduction in the Bacteroidetes/Firmicutes ratio was observed in MNV-1-infected C57BL/6 mice compared to mock-inoculated controls (101).…”
Section: Influence Of Murine Norovirus On Biomedical Research Modelsmentioning
confidence: 98%